(untitled) (Research, Society and Development, 2022)
Dispose of the importance of the role of nursing in caring for the victim of rape, to dimension the phenomenon with greater accuracy, identifying the victim of aggression, implementing protocols and regulations of existing public policies, amplifying the role of nurses in the preservation of traces in consolidation of a health model that incorporates universality and equity. Methodology: This is a primary descriptive explanatory applied review of a resolute quantitative nature, with a selection of articles published between the years 2013 to 2021, in the LILAC, BVS, BDENF and Google academic databases. Result: The screening of the article followed the PRISMA recommendation, from the syntheses evidenced, 48 articles emerged, which after selection, eight composed the review. Conclusion: It is necessary to build knowledge for the professional nurse, in a new perspective in the evolution of care with comprehensive care, with guidelines for the professional development of health and strategies with greater scope and sensitivity to women victims of sexual violence.